Analisis Penerapan Sistem Informasi Manajemen Kepegawaian (Simpeg) di Subbagian Umum Kepegawaian Dinas Pendidikan Kabupaten Bekasi - Amelia Nova Agustin; Eka Yulyana; Gun Gun Gumilar (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine, examine and analyze the application of e-government in the application of the Personnel Management Information System (SIMPEG) in the General Subsection of Personnel at the Bekasi Regency Education Office. This research is a descriptive qualitative type with data collection techniques carried out through triangulation which includes interviews, observations and documentation studies, then the data is analyzed using the Miles and Huberman model where the data is reduced, presented and drawn conclusions. The results of the discussion refer to the theory of E-government according to Indrajit, 2004 which has three supporting dimensions in the form of value, support and capacity. The results of this study are the Personnel Management Information System (SIMPEG) has been running quite well but on the one hand it has not met optimally in the realm of human resources and proper room capacity.